Driving under the influence of cannabis among recreational and medical cannabis users: A population study. (September 2022) - Wickens, Christine M.; Stoduto, Gina; Ilie, Gabriela; Di Ciano, Patricia; McDonald, André J.; Mistry, Aditi; Alawi, Aisha; Sharma, Smriti; Hamilton, Hayley; Nigatu, Yeshambel T.; Elton-Marshall, Tara; Mann, Robert E.
Abstract: Background: Comparisons of individuals using cannabis for medical versus recreational purposes have identified differences in health status, alcohol and drug use, and perceived risk of drug use. All of these factors are associated with aggressive and impaired driving and collision risk. Yet, few studies comparing medical and recreational cannabis users have considered differences in driver behaviour and road safety. Aim: This study examined the association between type of cannabis use (medical versus recreational-only) and engaging in driving under the influence of cannabis (DUIC), controlling for suspected confounding variables. Method: Data were derived from a regionally stratified cross-sectional general population telephone survey of adults (18+ years) in Ontario, Canada conducted from 2014 to 2019. Respondents reporting past-year operation of a vehicle and past-year use of cannabis were selected (N = 1392). A binary logistic regression was conducted to assess the association between type of cannabis user (medical versus recreational-only) and self-reported DUIC, controlling for cannabis use frequency, hazardous drinking, perceived general and mental health, demographic characteristics, driving exposure, and interview year. Results: In total, 9.7 percent of recreational-only users reported DUIC compared to 27.0 percent of medical users. Adjusting for covariates, medical cannabis users had almost two times greater odds of DUIC than recreational-only users (AdjOR = 1.78, p = .037, 95%CI = 1.03, 3.05). Discussion: A higher proportion of medical cannabis users, relative to recreational-only users, engaged in DUIC. This finding has important implications for improving the effectiveness of public health interventions designed to reduce DUIC. Further research examining the harms of medical versus recreational cannabis use for road safety is needed. Highlights: Examined population-level survey data from Ontario, Canada. Among cannabis users, 65.5% use for recreational purposes only and 34.5% use medically. Medical users had greater odds of driving under the influence of cannabis than recreational-only users.